SYNERGISTIC EFFECT OF SPERM FILTRATION TECHNIQUES AND ANTIOXIDANTS ADDED TO EXTENDER OF IRAQI BUFFALO SEMEN - Saif N. Alwaeli; S. M. Eidan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study investigated the synergistic effect of glass wool and sephadex sperm filtration techniques on improving the low semen quality of buffalo bulls with or without antioxidants. Semen was collected for 14 weeks, evaluated weekly, and divided into 12 groups. Good and low semen have extended using a Tris extender. Good semen quality is divided into three groups [S1: Tris extender; S2: Tris + vitamins E (2 mM) and C (5 mM); S3: Tris + glutamine (20 mM) and arginine (1 mM)]. Low semen quality was divided into three main groups and subdivided into three sub-groups (S4; Tris extender; S5: Tris +vitamins E (2 mM) and C (5 mM); S6: Tris + glutamine (20 mM) and arginine (1 mM)). In the 2nd and 3rd main groups, glass wool and sephadex techniques are used with or without adding vitamins (E+C) and amino acids (Glutamine and arginine) and subdivided into three sub-groups with each technique, referred to as S7–S9 for glass wool and S10–S12 for sephadex techniques. Improving (P<0.01) motility, normal morphology, acrosome, and plasma membrane integrity and reducing total sperm abnormalities of low semen quality were noticed using sephadex with or without adding vitamins or amino acids post-cryopreservation. In conclusion, the sephadex technique removed immotile sperm, dead, abnormal, and good sperm harvested by this technique, which in turn may reflect positively on improving the pregnancy rate.